classification of d.c glow discharge regions by fuzzy logic technique - Nabhan AbdulKareem Hamdoon (College of Education for Pure Sciences, 2013)
ABSTRACT A fuzzy logic model was constructed to classify the d.c glow discharge regions (Townsend dark region, glow discharge region, arc discharge) which including the design of computerized fuzzy inference system that depends on one of the intelligent techniques (Fuzzy logic). Their input consists of linguistic variables describing the fundamental parameters (current, voltage) of standard (I-V) curve of electrical discharge, and their output consists of three linguistic variables(dark, glow, arc) that describe the d.c. electrical discharge regions. It is suggested in this study that three different types of Gaussian membership functions in different forms for each variable. The results seem to be a good compatible with other published researches, making use of the MATLAB scientific software version 7.6.0.324 (R2008a